Routledge handbook on victims' issues in criminal justice - Roberson, Cliff (Routledge handbooks, 2017)
pt. I. Introduction to victims' rights -- Issues in victim services -- Federal victims' legislation -- Victims' assistance programs' reforms -- Victims in criminology theory -- Victims' rights legislation: comparative assessment and implementation issues -- pt. II. Victim issues regarding specific types of victimization -- Expanding the conceptualization of survivor in sexual assaults -- Intimate partner violence, neoliberal ideologies, and controversies about victimhood -- Why me : understanding cybercrime victimization -- Hate crime victimization -- Counseling families of murdered victims : a therapeutic perspective -- Members of the LGBT community as victims of crime -- pt. III. Victim services -- Enhancing service provider systems -- Special needs of elderly victims -- Factors surrounding providers' views of Latina immigrant victims -- Victim impact statements : understanding and improving their use -- Victims' needs and restorative justice -- Helping assault victims -- Victim witnesses in investigative interviews and court processes -- pt. IV. Victim service organizations -- History of the World Society of Victimology -- Victimology and victims' service organizations -- Victims and the media.